2021
DOI: 10.3389/fpsyt.2021.710515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Disclosure on Loneliness in Adolescents During COVID-19: The Mediating Role of Peer Relationships

Abstract: Long-term home isolation has had a certain impact on adolescents' enthusiasm for interpersonal communication and desire for self-disclosure during COVID-19. The purpose of this study was to explore the relationship between adolescents' self-disclosure and loneliness during COVID-19, and to analyze the mediating role of peer relationship in it. We conducted a cross-sectional study involving 830 Chinese adolescents (males: 47.5%, Mage14.25 years; females: 52.05%, Mage 14.19 years; Age range 12-15). Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
10
0
5
Order By: Relevance
“… 47 Peer acceptance was associated with better mental health. 111 Not having any friends, missing friends and having fewer friends were associated with negative mental health and substance abuse in Indonesia and Brazil. 43 , 44 , 71 …”
Section: Resultsmentioning
confidence: 97%
“… 47 Peer acceptance was associated with better mental health. 111 Not having any friends, missing friends and having fewer friends were associated with negative mental health and substance abuse in Indonesia and Brazil. 43 , 44 , 71 …”
Section: Resultsmentioning
confidence: 97%
“…They are compelled to lock themselves down comprehensively, and find it harder to articulate their feelings during the COVID-19 pandemic, which has caused a persistent influence on the mental health of children and adolescents and ultimately contribute to the occurrence of depressive symptoms (29). It was found in a domestic study that the occurrence of emotional difficulties in children and adolescents is much higher than that before the pandemic (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated self-disclosure as a prerequisite for healthy adjustment (33). An individual with positive self-disclosure can have effective communication with the outside world (30). On the other hand, non-disclosure is often used to refer to non-expression, inhibition, or topic avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that intimate disclosure to peers was associated with levels of happiness but did not survive correction for multiple comparisons. Recent studies found that increased peer connections, and specifically peer-directed disclosures, were related to lower feelings of loneliness and greater well-being during COVID-19 (Chen et al, 2021;Li et al, 2021). Peer relationships play a crucial role in the development of self-identity through discussion of shared values and interests (Pfeifer & Berkman, 2018), and continued interactions with peers (either online or in person) are likely to be foundational for supporting these developmental processes during the pandemic (Orben et al, 2020).…”
Section: Individual Differences In Disclosure Value and Mental Healthmentioning
confidence: 99%